Comparison Between Green And Chemical Synthesis Of Copper Nanoparticles: Characterization And Antibacterial Activity - M. Ibrahim, Dalal; S. Bendaba, Rania; a yaakub Hesien, Rehab (Scientific Journal of University of Benghazi, 2025)
Nanoparticles are often associated with their small size and numerous applications. The synthesis process is equally important since it determines the size and properties of the nanoparticles. Additionally, green synthesis provides an economical, ecologically beneficial, and sustainable substitute. Researchers have focused on copper nanoparticles (NPs) due to their unique characteristics, which include optical, antibacterial, and electrical capabilities that depend on size and form. Two techniques are becoming more well-known in this field for producing silver nanoparticles. The green method and chemical reduction were used to create copper nanoparticles, and the two samples’ optical, antimicrobial, and structural properties were examined. An extract derived from lemon fruit was incorporated into the environmentally friendly procedure. Furthermore, trisodium citrate was used as a reducing agent in the chemical procedure, and several techniques were used to characterize the nanoparticles. These techniques include X-ray diffraction (XRD), ultraviolet-visible spectroscopy (UV-Vis), scanning electron microscopy (SEM), and antibacterial activity. The XRD analysis revealed that the particles were crystalline in form and that the green-produce variation’s crystal sizes (4.6 nm) were greater than those of the chemical reduction variant (2 nm). The shape of the chemically produced nanoparticles is unclear, whereas the green approach coats the generated nanoparticles with the biological materials in lemon extract. The antibacterial evaluation was completed using the agar well diffusion method. The particles’ SEM images showed that they were aggregating into polyhedral and leaf-shaped particles. In the aqueous solution containing copper nanoparticles, the chemically generated absorption peak was located at 300 nm in the UV-visible spectrum, whereas the green synthesized absorption peak was located at 260 nm. This included Escherichia coli O157:H7 and Staphylococcus aureus as the bacteria in the medium. The green had a larger zone of bacterial growth inhibition. synthesized variant in different concentrations of 20 mg, 40 mg, and 60 mg, which were 22 mm, 25 mm, and 28 mm in Escherichia coli and 14 mm, 24 mm, and 26 mm in Staphylococcus aureus, respectively. Conclusions: The improved antibacterial responses of the green-produced versions were caused by the accelerated rate at which the organic chemicals in the lemon fruit extract stabilized the nanoparticles.